2006
DOI: 10.1038/nn1737
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of dopamine D2 receptors during chronic cocaine self-administration in monkeys

Abstract: Dopamine neurotransmission is associated with high susceptibility to cocaine abuse. Positron emission tomography was used in 12 rhesus macaques to determine if dopamine D2 receptor availability was associated with the rate of cocaine reinforcement, and to study changes in brain dopaminergic function during maintenance of and abstinence from cocaine. Baseline D2 receptor availability was negatively correlated with rates of cocaine self-administration. D2 receptor availability decreased by 15-20% within 1 week o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
351
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(391 citation statements)
references
References 40 publications
30
351
1
3
Order By: Relevance
“…labeled benzamide derivative that binds reversibly to D2 receptors [81] . In PET imaging with [ 18 F] FCP, Nader and colleagues [82] found that the baseline D2 receptor availability is negatively correlated with the rate of cocaine self-administration.…”
Section: Pet Studies Of Postsynaptic Da Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…labeled benzamide derivative that binds reversibly to D2 receptors [81] . In PET imaging with [ 18 F] FCP, Nader and colleagues [82] found that the baseline D2 receptor availability is negatively correlated with the rate of cocaine self-administration.…”
Section: Pet Studies Of Postsynaptic Da Receptorsmentioning
confidence: 99%
“…labeled benzamide derivative that binds reversibly to D2 receptors [81] . In PET imaging with [ 18 F] FCP, Nader and colleagues [82] found that the baseline D2 receptor availability is negatively correlated with the rate of cocaine self-administration.[ fallypride PET imaging study, nicotine-dependent smokers displayed signifi cantly less availability of D2/D3 receptors within the bilateral putamen, functionally covering parts of the dorsal striatum, compared to never-smoking subjects [83] .[ 18 F] desmethoxyfallypride ([ 18 F] DMFP), another selective D2/D3 receptor antagonist, has also been developed and used to fi nd that a low availability of D2/3 receptors in the ventral striatum and adjacent putamen is associated with a high level of craving for alcohol [33] .For the D1 receptor, [ 11 C] NNC 112, a new benzazepine [(+)-8-chloro-5-(7-benzofuranyl)-7-hydroxy-3-methyl-2,3,4,5-tetra-hydro-lH-3-benzazepine], has been reported to be a useful PET radioligand for the quantitation of D1 receptors in humans [84] , and its D1 receptor selectivity has recently been re-evaluated [85] . With PET and the radiotracer [ 11 C] NNC 112, Martinez et al [86] found no difference between cocaine abusers and normal controls.…”
mentioning
confidence: 99%
“…Volkow Tomasi et al, 2010), as highlighted by Colzato et al (2009a) it is also possible that a number of pre-existing factors might account for the observed cognitive deficits either directly or via increasing the likelihood that certain individuals will use the drug. Such vulnerability factors might include cognitive disturbance (Bechara, 2005), dopaminergic receptor dysfunction (Nader et al, 2006) or preexisting personality traits, such as impulsivity (Verdejo-Garcia et al, 2008) or schizotypy.…”
Section: Introductionmentioning
confidence: 99%
“…1−6 Modulation of the dopaminergic pathways is also thought to occur as a consequence of acute or chronic abuse of pyschostimulants. 7,8 Previous studies have defined two types of dopamine receptors, the D1-like (D1 and D5 subtypes) and D2-like (D2, D3, and D4 subtypes) receptors. D1-like receptors are linked to the activation of adenylyl cyclase via coupling to the Gs/Golf class of G proteins.…”
Section: Introductionmentioning
confidence: 99%